Perilaku Investor Herding pada Perusahaan Infrastruktur di BEI: Pendekatan Panel Data - Hartaty Hadady; Rachman Dano Mustafa (Society, 2022)
This research aims to examine the behavior of herding investors due to the information on interest rates and trading volume. By using daily infrastructure company data on the IDX, it is found that interest rates have a negative effect, while volume has a positive effect on herding behavior. The results show that herding behavior decreases when information on interest rates is entered, while herding behavior increases when there is a trend in trading volume. These results indicate that information announced and scheduled will reduce the behavior of herding investors, such as information about interest rates. On the other hand, investor herding behavior tends to increase when information is random, such as trends in stock trading volumes.